2015
DOI: 10.1038/ejhg.2015.169
|View full text |Cite
|
Sign up to set email alerts
|

Rare FOXC1 variants in congenital glaucoma: identification of translation regulatory sequences

Abstract: Primary congenital glaucoma (PCG) is the cause of a significant proportion of inherited visual loss in children, but the underlying mechanism is poorly understood. In this study, we assessed the relationship between PCG and FOXC1 variants by Sanger sequencing the proximal promoter and transcribed sequence of FOXC1 from a cohort of 133 PCG families with no known CYP1B1 or MYOC mutations. The pathogenicity of the identified variants was evaluated by functional analyses. Ten patients (7.5%) with no family history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…In addition, approximately 5% of the patients in these cohorts carried GPATCH3 rare variants in the heterozygous state. Segregation analysis of these variants failed to reveal a monogenic inheritance, but their elevated frequency among patients and the predicted functional impact for most of them suggest that they are disease-causing variants that may be involved in non-monogenic congenital glaucoma in accordance with our previous findings671219. Also in accordance with this hypothesis, a recent study reported that 10 of 189 unrelated PCG families carried heterozygous rare variants in the TEK gene with dominant transmission and highly variable expressivity, which was explained by stochastic developmental events or oligogenic/digenic inheritance24.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, approximately 5% of the patients in these cohorts carried GPATCH3 rare variants in the heterozygous state. Segregation analysis of these variants failed to reveal a monogenic inheritance, but their elevated frequency among patients and the predicted functional impact for most of them suggest that they are disease-causing variants that may be involved in non-monogenic congenital glaucoma in accordance with our previous findings671219. Also in accordance with this hypothesis, a recent study reported that 10 of 189 unrelated PCG families carried heterozygous rare variants in the TEK gene with dominant transmission and highly variable expressivity, which was explained by stochastic developmental events or oligogenic/digenic inheritance24.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, many studies have shown that variants in non-coding regions of the genome can cause ocular disorders (Bhatia et al 2013;Chatterjee and Pal 2009;Cipriani et al 2017;Conte et al 2015;Davidson et al 2016;Small et al 2016;Volkmann et al 2011). Although ocular genetic diseases generally follow a Mendelian pattern of inheritance, mutations in the non-coding regions of the genome (as well as some coding regions) have also been associated with non-Mendelian inheritance (Medina-Trillo et al 2016). Variants in non-coding regions (~98% of the genome) represent almost 2% of known gene disruptions responsible for human inherited disease according to the Human Gene Mutation Database (http://www.hgmd.cf.ac.uk/ac/index.php).…”
Section: -Diagnostic Strategymentioning
confidence: 99%
“…The first identified and most prevalent cause of recessive PCG is CYP1B1 loss-of-function (LoF) (Sarfarazi and Stoilov 2000;Stoilov et al 1997), which is present in 18%-48% of non-consanguineous European patients (Campos-Mollo et al 2009;Colomb et al 2003;López-Garrido et al 2013;Weisschuh et al 2009). Additional genes reported to play a role in this pathology are LTBP2 (Ali et al 2009), MYOC (Kaur et al 2005), FOXC1 (Medina-Trillo et al 2016;Medina-Trillo et al 2015), TEK (Souma et al 2016) and GPATCH3 (Ferre-Fernández et al 2017), illustrating the genetic heterogeneity of this disease.…”
Section: Introductionmentioning
confidence: 99%